Voxel-based point kernel method for dose rate assessment of non-uniform activity and self-shielding sources in nuclear facility decommissioning. (November 2019) - Yang, Li-qun; Liu, Yong-kuo; Peng, Min-jun; Ayodeji, Abiodun; Chao, Nan
Abstract: Decommissioning task in nuclear facilities results in a number of radioactive components with non-uniform activity and self-shielding sources. Previous applications of virtual reality technology in the literature did not consider self-shielding sources and the activity distribution of sources is always considered homogeneous (uniform). In order to calculate the ambient dose equivalent rate of non-uniform activity and self-shielding source after cutting and removal operations in nuclear facility decommissioning, this paper proposes a hybrid of voxelization algorithm and point-kernel method for advanced gamma dose rate assessment for cutting simulation in a radioactive environment. The initial 3D scene model was designed using 3dsMax modeling and imported as a 3DS format file. The source solid models of arbitrary shape are automatically converted to voxelized models according to the voxelization algorithm. The cutting paths of the voxelized models are imported by the G-Code programming language. After the cutting and removing operations, the voxelized source models are compressed. Ultimately, considering the non-uniform distribution of the activity and self-shielding of sources, the gamma dose rate distribution is obtained by voxel-based point-kernel calculation. Simulation results are compared with dose rate calculated with MCNP, which show that the proposed method can produce a fast and accurate simulation of the cutting and removal operations of radioactive components and effectively calculate the ambient dose equivalent rate of non-uniform activity and self-shielding sources. Highlights: The method simulates the cutting and removal operations of radioactive components. The method calculates dose rate of self-shielding and non-uniform activity sources. The arbitrarily shaped solid models are converted into voxels. The voxelized sources are compressed to improve time efficiency.